The Impact of Political Variables on the Growing External Migration of Iraqi Youth from a Geopolitical Perspective - Al-Ahbabi, Naseef (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية; Vol 26 No 10 (2019): Journal of Tikrit University for HumanitiesDO - 10.25130/hum.v26i10.844, 2019)
Iraq enjoys strategic importance distinct politically and economically as it contains the advantages of location in addition to the available resources of manpower and hydrocarbons, which made this country a point of conflict for global forces aimed at dominating the oil wealth and the displacement of young groups on which to build the pillars of the power of the State in terms of the development of ideas. However, the extent to which these ideas are translated into pilot projects that enhance the capabilities and qualifications that make Iraq a regional and alliance power with its regional environment in accordance with cooperation and economic relations. Embodied in the centers of power actors on the political map in the Middle East, including Turkey, the strategic dimension in support of Iraq to get out of these crises and events that make it a geopolitical decline has helped to increase the foreign migration of young people from Iraq to the world countries, as the importance of this study through the comprehensive geographical view of the situation of Iraqi youth and repercussions. The political crisis that he is going through in the light of political and economic variables, which made him suffer from a weak point in political decision-making towards the youth group, which embodies a human force can be invested in many areas gives the state strength and vitality despite the presence of a foreign agenda is working Hadfha to prevent political instability has. Is the role of the Iraqi government in containing the situation of Iraqi youth, and whether oil plays a role in the fabrication of the migration crisis of Iraqi youth, and whether the political events and regional and international changes in the Middle East is a real reflection on the deterioration of the situation of young people in Iraq, The scientific hypotheses as a geopolitical assessment of the problem of scientific research is that Iraq must recognize that it is a regional power, its strategic food and national will, which help to reach and contribute to political decision-making, contain these human energies and create real opportunities for investment. Despite the continued aggravation of the Iraqi youth crisis under the policies that are based on unilateralism in the resolution and thus weakened the role of Iraq regionally and internationally geographical perspective, and continue to decline geopolitical work to break the social fabric and social exclusion in it and then strengthen the role of the external agenda in the country's march towards the abyss A thousand young people have been forced to emigrate from the perspective of contemporary geopolitics.  The analysis of power is also used as a tool to measure political sentiment, not to mention the adoption of official data and documents available by local, regional and international bodies and institutions, as we conclude from the above that the situation of young people in Iraq suffers from the exclusion of the most basic rights that must be available to them In spite of the importance of the strategic and political that Iraq possesses, but did not translate it in its real form in the investment of the youth, which is a form of measuring the strength of the state, more than that dissonance and lack of consensus on the national will to promote the political reality was A large living in the face of those working class , Despite the attraction and convergence to resolve the crisis suffered by Iraqi youth through political entities and parties, and work to reduce and stand against the external agenda and supported by the political systems aimed at fragmentation of this country, which contains the treasures of the dimension of civilization and history full of glories of Iraqi youth according to the geopolitical perspective Contemporary.